Pengaruh Pengawasan Kerja, Pengarahan, Perencanaan Kerja Dan Pelatihan Terhadap Prestasi Kerja Anggota Polres Lahat - Agustiansyah, Nano; Aprini, Nisma; Darmin (Jurnal Pusat Manajemen, 2025)
This study aims to determine the Effect of Work Supervision, Direction, Work Planning and Training partially and simultaneously on the Work Performance of Lahat Police Members. The sampling method used is Incidental sampling. In this study, the research sample was all 32 police members at Lahat Police. Instrument validity testing used person's product moment correlation, while reliability testing used Alpha Cronbach. Data analysis used multiple regression analysis. The results of the analysis show that: 1). There is a positive and significant influence between work supervision on work performance of t count 5.733 with a significance value of 0.000 <0.05. 2) there is a positive and significant influence between direction on work performance with t count 3.434 with a significance value of 0.008 > 0.05. 3) There is a negative and insignificant influence between work planning on work performance of t count -0.175 with a significance value of 0.862 > 0.05. 4) There is a negative, insignificant effect between training and work performance, with a t-value of -0.711 and a significance value of 0.483 > 0.05. 5) There is a significant, positive effect between the variables of Work Supervision, Direction, Work Planning, and Training simultaneously on the Work Performance of Muara Lahat Police Officers, with a calculated F-value of 12.977 and a significance value of 0.000 < 0.05.